Digital Literacy and Training Ms. Office Excel - Adi Candra; Farida; Andi Nurul Faizah; Husni Sulaiman (Jurnal Visi Pengabdian Kepada Masyarakat, 2025)
Tamalanrea Village is one of the villages registered as a smart village, so it is hoped that all residents understand and are able to apply technology. However, the usefulness of technology in this society is still not optimal, due to the lack of outreach and seminars related to current technological developments. The implementation method for this service is by using the following method: (1) lecture, this method is used to convey digital literacy which provides understanding and explanation to the public regarding the use of social media and how to be wiser in its use among the local community. (2) Demonstration, this method is used for an effective learning approach, to help participants understand complex concepts and develop practical skills. In carrying out this activity, an evaluation stage is carried out which is a very important activity carried out in service activities as a benchmark for the extent of the participants' abilities after participating in the training. The results of this literacy and training enable the community and village officials to understand and understand the ways and methods that need to be used in using social media and current data processing technology.